Effect of Crip Walking On Walking Abilities in Community Dwelling Older Adults - Sakshi R, Sawant; Satyam S , Bhodaji (Journal of Neonatal Surgery, 2025)
Abstract Background: Walking ability can be severely hampered by age-related physiological changes in older persons, which raises the risk of falls and functional deterioration. Even if they work, traditional rehabilitation techniques can have little engagement, which leads to poor adherence. This research investigates the use of Crip Walking, a rhythmic street dance with quick footwork and dynamic balancing demands, as a creative intervention to enhance older individuals' gait and mobility. Method: In this randomized controlled trial, 50 community-dwelling older adults from age 60 and above were recruited. Participants were randomly assigned to either the Crip Walking intervention (n=25) or the High-Resistance Training (HRT) intervention (n=25). Both interventions were delivered three times weekly for four weeks, with each session lasting 45–60 minutes. The primary outcomes were the Dynamic Gait Index (DGI) and Timed Up and Go (TUG) test, which were assessed pre- and post-intervention. Results: It is notable that improvement in both DGI and TUG scores (p<0.001) was seen in both groups. The Crip Walking group, though, showed greater improvements compared to that of the HRT group, with a higher post-intervention DGI (22.68 ± 1.6) and shorter TUG time (9.47 ± 1.27 seconds) compared to the group (DGI: 21.28 ± 1.49; TUG: 10.33 ± 1.60 seconds). Conclusion: Crip Walking is a enjoyable, and effective intervention to improve gait, balance, and mobility in older adults. Its engaging, rhythmic style may increase adherence and provide a culturally inclusive substitute for conventional rehabilitation.